Estudo funcional de genes de reparo de DNA superexpressos em glioblastoma multiforme - Sousa, Juliana Ferreira de [UNESP] (2015)
Gliomas are the most common type of primary brain cancers. They are pathologically defined by the presence of histological and immunehistochemical characteristics that evidence glial differentiation. According to the hypothetical cell of origin they are classified in: astrocytomas, oligodendrogliomas and ependimomas. Among them, astrocytomas are the more common and aggressive type. The treatment currently used for GBM includes surgical resection of tumor followed by chemotherapy with temozolamide (TMZ) and radiotherapy, but this protocol is still insufficient due to the high resistance of cancer cells. Searching for repair genes associated with the high resistance of astrocytomas, we developed a previous study of differential gene expression using a collection of DNA repair genes. In this analysis, we identified seven genes significantly overexpressed in glioblastoma multiforme (GBM), namely: APEX1, BRCA2, BRIP1, EXO1, NEIL3, RAD54L and XRCC2. Using quantitative RT-PCR, we evaluated the expression of these genes in an expanded panel of samples with 54 clinical cases of different grade astrocytomas and five GBM cell lines. All genes showed expression significantly higher in astrocytomas, except RAD54L in grade II astrocytomas. Moreover, the overexpression of this 7 genes evaluated individually doesn't exert direct influence upon patient's survival rate. Remarkably, EXO1 and NEIL3 showed the higher fold changes and were chosen for functional silencing assays. This experiments were performed with T98G and U138MG cell lines that showed the higher expression levels among the GBM cell lines analyzed. In the functional assays, we observed that the silencing of EXO1 or NEIL3 doesn't induce changes in the apoptosis and cell death rates and doesn't change the distribution of cells in cycle. Beyond this, the silencing of this two genes doesn't sentisizes cells to ionizing radiation.